Kualitas Pelayanan Publik Bidang Administrasi Kependudukan pada Program Paket Layanan (PAKLAY) Satu Hari Jadi di Kantor Desa Gaum, Kecamatan Tasikmadu, Kabupaten Karanganyar - Widyantoro Yuliatmojo; Anita Tri Utami; Nindita Pramuktisari; Roni Prihanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Gaum Village, located in Karanganyar Regency, actively administers public services in the field of population administration. To cut bureaucratic red tape, the village government implemented an innovative